Belgrade Professors at CEU
Audio recording of the conference held at CEU with Belgrade University professors where they describe the consequences of a Serbian law affecting their universities and the academic life. Moderator: Prof. Tibor Várady from CEU. Key speakers in the panel: Prof. Zagorka Golubovic, Prof. Vladeta Jankovic and Prof. Vesna Rakic Vodinelic. The members of the panel participated in an intensive question and answer session with the media and CEU representatives and guests. Among the personalities questioning the lecturers was CEU Academic Pro-Rector. Prof. Sorin Antohi.